دراسة سلوك واستقرار الجدران الاستنادية الحجرية المصنعة (SRW) تحت تأثير الأحمال الستاتيكية والزلزالية - مالك حسن; رشاد السيروان (Tishreen University, 2017)
تعتبر الجدران الاستنادية من أكثر أنواع المنشآت الهندسية انتشاراً وكانت الجدران الاستنادية تنفذ من الأحجار الطبيعية قبل اكتشاف البيتون، حيث تعتبر الحجارة الطبيعية من أوائل المواد التي استخدمها الانسان في بناء المنشآت الهندسية منذ آلاف السنين، وتشهد على ذلك العديد من المنشآت في الحضارات القديمة التي لاتزال آثارها موجودة حتى الآن. و بعد اكتشاف البيتون و البيتون المسلح قلت نسبياً الجدران الاستنادية المنفذة من الأحجار الطبيعية، ولكن رغم هذه السنين لم تفقد ألقها و بريقها حتى الآن، و ازداد الاهتمام في السنوات الأخيرة بمواد البناء الجديدة التي تتركب من أحجار مصنعة حيث تم استخدامها إلى جانب مواد البناء التقليدية في عدة مجالات سواء في الهندسة الجيوتكنيكية أو الأبنية ....الخ, فهي لا تقدم حلولا تقنية بسيطة وحسب بل تعتبر مرغوبة بشكل كبير لأسباب جمالية و لسهولة تنفيذها و مقاومتها للعوامل الخارجية ، إضافة إلى انها تقدم حلولاً اقتصادية بكلفة محدودة مقارنة بالجدران الاستنادية التقليدية من البيتون المسلح. و هذا البحث يتناول دراسة سلوك هذه الجدران الاستنادية الحجرية تحت تأثير الأحمال الستاتيكية و الديناميكية ودراسة بارامترية لأهم العوامل المؤثرة على استقرار هذه الجدران. The retaining walls are one of most types of engineering constructions and it have built from natural stones before discovering concrete, Where natural stones have considered one of the early human materials used in building engineering constructions for thousands of years, and many facilities in ancient civilization still existing effects so far, And after the discovery of the concrete and reinforced concrete, the retaining walls which was built from natural stones diminished relatively Despite the years this retaining walls has not lost its luster and brilliance, and there is increased interest in recent years in using new building material which consists of manufactured stones where used together with traditional construction materials in several areas both in geotechnical engineering or building ... Etc . This retaining walls present simple technical solutions and it is desirable for aesthetic reasons and simple implementation and resistance to external conditions, In addition to being economical solutions limited cost compared to traditional reinforced concrete retaining walls. This research deals with the study of the behavior of Segmental Stone Retaining Walls (SRW) under the static and dynamic loads and parametric study of the most important factors which influence stability of these retaining walls